Privatizing sick pay: Does it work? - Pierre Koning (IZA World of Labor, 2016)
Public schemes for sickness benefits and disability insurance are often criticized for the lack of incentive they provide for preventive and reintegration activities by employers. To stimulate the interest of employers in engaging with these schemes, several modes of privatization could be considered, including the provision of sickness benefits by employers, “experience rating” of disability insurance costs, employer self-insurance, or insurance by private insurance providers. These types of employer incentives seem to lower sickness rates, but they also come at the risk of increased under-reporting and less employment opportunities for workers with disabilities or bad health conditions. Policymakers should be aware of this trade-off.
Keywords: H32; H55; K32; 330; sickness; disability insurance; employer incentives; privatization